SIMULATION LAYOUT PROPOSAL IN A BRAZILIAN TEXTILE INDUSTRY : PROPOSTA DE LAYOUT DE SIMULAÇÃO EM UMA INDÚSTRIA TÊXTIL BRASILEIRA - Rodrigues, Thales Volpe; Queiroz, Lucas Marcos Silva; Ferreira Junior, José da Silva; Sanjulião , Lo-Ruana Karen Amorim Freire; Oliveira, Nathan Peixoto (Brazilian Journal of Production Engineering, 2020)
The analyzed textile industry has been one of the main branches of production in the city and region for a long time, mainly in the manufacture of lingerie and accessories. Due to the demands of the national economic scenario and the vast local competition, obtaining good production planning and tools that help reduce costs become essential objects for the company to remain in the market. Based on these issues and the lack of knowledge of available technological resources, this work aims to carry out a layout study in the industrial sectors, seeking to reduce the movement and transportation of employees. The research method presented refers to modeling and simulation, using tools such as the IDEF-Sim and the ProModel®computer software, which offers the possibility of identifying inefficiencies in the production process and, based on this identification, proposing improvements in more efficiently using available resources. As a result, there was an improvement in the modified simulated model of more than 45% in the final production of the container, in addition to the reduction in the movement that generated the reduction of employees in the sector, the optimization of the manufacturing space and quality improvement.